Faktor-Faktor Yang Mempengaruhi Service Per Conception Pada Sapi Bali di Desa Kali Pasir Way Bungur Lampung Timur - Wati, Novi Eka; Ahmad, Irsyad; Wicaksana, Kunaifi (JDP: Jurnal Dunia Peternakan, 2023)
The purpose of this study was to determine the range of service per conception and the factors that influence the service per conception of Bali cattle in Kalipasir Village, Way Bungur, East Lampung Regency. The material from breeders and inseminators is the reproduction record of 50 Bali cattle. The results of this study include the average service per conception which is 1.74 ± 0.31 classified as ideal. Factors that affect the service per conception of Bali cattle, namely the last education and drinking water supply system. The conclusion in this study is that service per conception is ideal 1.74 ± 0.31. The latest education and drinking water supply system have a positive impact on the service per conception of Bali cattle. Key words : factor, Service per conception, Bali cattle.